Non-Hodgkin’s lymphoma of nasopharynx diagnosed during pregnancy (a case from practice) - Kitsera, N.; Helner, N.; Kitsera, O.; Osadchuk, Z. (Experimental Oncology, 2011)
The article presents the case of 32 years old woman with non-Hodgkin’s lymphoma of the nasopharynx who received the anticancer treatment at 21-26 weeks of pregnancy (20 courses of radiation in dose of 40 Gy on the right half of the nasopharynx). The pregnancy was performed by cesarean section at the term of 32 weeks, and a healthy girl was born. Timely diagnosis and correct treatment of non-Hodgkin’s lymphoma give the woman a chance to have a healthy child.